The Abolition of Mandatory Military Service in Iraq after 2003 and Its Impact on Educational Decline and Moral Commitment among the New Generation - Mustafa, Dr. Elaf Asim Mustafa; Al-Shammari, Dr. Emad Al-Shammari (Sulaimani Journal for Humanities, 2026)
This research addresses a highly important topic: mandatory conscription after 2003 and the developments and consequences following its abolition. The study examines how the conscription system was implemented in the years prior to 2003 and its negative effects on society. It also explores the adverse consequences of abolishing this system, including the spread of numerous social problems such as youth unemployment, drug abuse, and the low educational attainment of a large segment of the youth population. These issues pose medium- and long-term risks to social security and cohesion. The research further proposes several solutions to these problems, including encouraging youth to participate in military service through financial incentives. This could be achieved by enacting laws to increase the salaries of conscripts and combating any negative phenomena that contributed to the rise of these social issues among the youth. This study traces the history and evolution of the mandatory conscription system, beginning with its establishment in the Ottoman era when Sultan Mahmud II introduced it in the summer of 1826. The system was subsequently extended to the provinces of the Ottoman state, excluding Baghdad, Mosul, and Basra, which impacted the registration of citizens for conscription purposes. Following the founding of the Iraqi state in 1921, the conscription system underwent gradual historical development until 2003, when it was ultimately abolished, which is the focal point of this study.
Keywords: Mandatory Military Service; Iraq; Social Impact; Youth Unemployment; Education; Moral Commitment